Probabilistic seismic hazard analysis on Ortigas Center - Saroca, Edgar Mari S.
This research conducted a probabilistic seismic hazard analysis for Ortigas Center, Pasig City. Analysis was carried out using the earthquake source map and seismicity map for Metro Manila provided by the Philippine Institute for Volcanology and Seismology (PHIVOLCS). Historical observations of earthquake events were obtained from IRIS, GCMT, USGS, and PHIVOLCS. Earthquake data was analyzed statistically and its recurrence relationship was obtained using the Guttenberg-Richter Recurrence Law. Results of the investigation were presented in the form of peak ground acceleration (PSA) and pseudo-absolute spectral acceleration (PSA) with 5% damping. Based from these results, uniform hazard response spectra (UHRS) were constructed for the possibility of 50%, 10%, and 2% chance in 50 years. The mean PGA for 72, 475, and 2475 years return period were calculated to be 0.158g, 0.27g, and 0.458g respectively. While the maximum PSA for the said return periods were found to be 0.27g, 0.616g, and 1.145g, respectively.